2013
DOI: 10.1111/jvp.12048
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of tobramycin following intravenous, intramuscular, and intra‐articular administration in healthy horses

Abstract: The objectives of this study were to examine the pharmacokinetics of tobramycin in the horse following intravenous (IV), intramuscular (IM), and intra-articular (IA) administration. Six mares received 4 mg/kg tobramycin IV, IM, and IV with concurrent IA administration (IV+IA) in a randomized 3-way crossover design. A washout period of at least 7 days was allotted between experiments. After IV administration, the volume of distribution, clearance, and half-life were 0.18 ± 0.04 L/kg, 1.18 ± 0.32 mL·kg/min, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…Nevertheless, several medications are used intra-articularly, such as COs, hyaluronic acid (HA)/sodium hyaluronate (SH)/hyaluronate (HA), polysulfated glycosaminoglycans, sodium pentosan polysulfate, sodium chondroitin sulfate, somatostatin, N-acetyl- D-glucosamine, radiation synovectomy, dextrose prolotherapy, keratan sulfate orgotein, saline for washout, silicone, mucopolysaccharide polysulfuric acid ester, chloroquine, lactic acid solution, amikacin, gentamicin morphine, autologous serum, platelet-rich plasma, mesenchymal stem cells derived from bone marrow or adipose stromal vascular fraction, gene therapy using IL-1 antagonists, and ethanol. In addition, studies have used a topical liposomal formulation that contains diclofenac, lyophilized products from green-lipped mussel, extracorporeal shockwave, acupuncture, magnetic field, transcutaneous electrical nerve stimulation, therapeutic ultrasound, laser therapy, manual therapy, aquatic physical therapy and nutraceuticals food suplement (Uthman et al 2003;Caron 2005;Revenaugh 2005;Carmona et al 2007;Frisbie et al 2009;Goodrich and Nixon 2006;Santos et al 2009;Lindegaard et al 2010;Cayzer et al 2011;Kawcak et al 2011;Baccarin et al, 2012;McIIwraith et al 2011McIIwraith et al , 2012aCarmalt et al 2012;Lamas et al 2012;Vanderweerd et al 2012;Frisbie et al 2013;King et al 2013;Neuman et al 2013;Ferris et al 2014;Koenig et al 2014, de Grawn et al 2016. The use of controlled physical activity, as a complementary treatment, possibly improves the comfort level of the horse and decreases the inflammatory process (Kerbyson et al 2013).…”
Section: Possible Treatmentsmentioning
confidence: 99%
“…The PLGA itself was almost degraded in 35 days. Because of the rapid disappearance of the drug from intra-articular space into serum when its molecular form is injected, 35,36 the concentration would change dramatically and multiple injections would be needed. Therefore, a suitable DDS is an important factor to consider for administering statin into synovial space more effectively.…”
mentioning
confidence: 99%
“…The cytotoxicity of several antibiotics commonly used in equine practice (eg amikacin, gentamicin, ceftiofur sodium, tobramycin, enrofloxacin) on joint tissues have been evaluated in separate studies with varying results 19‐26 . Multiple studies have demonstrated the chondrotoxic effects of enrofloxacin in vitro, confirming the clinical observation of quinolone induced arthropathy in juvenile animals, which was found to be the result of irregular integrin signalling and reduced cartilage metabolism 24‐25 .…”
Section: Introductionmentioning
confidence: 89%